Quick identification of febrile neonates with low risk for serious bacterial infection: an observational study. Issue 1 (21st December 2006) - Marom, R; Sakran, W; Antonelli, J; Horovitz, Y; Zarfin, Y; Koren, A; Miron, D
Abstract : Objective: To examine the possible usefulness of simple and quick criteria for identifying febrile neonates with low risk for serious bacterial infection (SBI). Design: All febrile neonates who were admitted between August 1998 and August 2003 to the Pediatric Emergency Department, HaEmek Medical Center, Afula, Israel, and to the Poriya Hospital, Tiberias, Israel, were included in the study. The recommended evaluation of each neonate included details of medical history and a complete physical examination, including blood culture, erythrocyte sedimentation rate (ESR), white cell count (WBC), and analysis and culture of urine and cerebrospinal fluid. Other tests were carried out as necessary. Patients who met all the following criteria were considered to have low risk for SBI: (1) unremarkable medical history; (2) good appearance; (3) no focal physical signs of infection; (4) ESR <30 mm at the end of the first hour; (5) WBC 5000–15 000/mm 3 ; (6) a normal urine analysis by the dipstick method. Results: Complete data were available for 386 neonates. SBI was documented in 108 (28%) neonates, of whom 14% had a urinary tract infection, 9.3% had acute otitis media, 2.3% had pneumonia, 1.3% had cellulitis, 0.5% had bacterial meningitis and 0.5% had bacterial gastroenteritis. The overall incidence of SBI was 1 in 166 (0.6%) neonates who fulfilled the criteria compared with 107 in 220 (48.6%) in the neonates who did not fulfil the criteria (p<0.001). The negative predictive value for SBI of the combination of the low-risk criteria was 99.4% (95% confidence interval 99.35% to 99.45%). Conclusions: Fulfilment of the criteria for low risk might be a reliable and useful tool for excluding SBI in febrile neonates.